Images of Love and Romance, and the Lover's Description in Saadi ash-Shirazi's and Safi-id-Deen al-Hili's Ghazal Poems: A Comparative Study (Journal of the College of Languages (JCL), 2025)
Lyric literature, specifically poems of love and ghazal (flirtation), has a good representation in both Arabic and Persian literature, since most poets posed poems of this kind in various periods of time, and consequently, they enriched their products. They try to express about love which makes one of human feelings in so lovely imagery and simple language. And, they attempt at creating novel similes in describing the lover. In this paper, the researchers studied images of love and romance, and lover's description both literally and semantically within selected ghazal poems by both Saadi ash-Shirazi and Safi-id-Deen al-Hili by way of comparison.Both poets lived in approximate times and in neighbouring countries. Researchers found that thinking about love by the two poets was not only similar, but identical in talking about love and romance, and lover's description, and this represents a significant point in the study. This was supported by many examples to prove their viewpoint. Then, they stated the appropriate conclusions.